Volume 6: Turbo Expo 2003, Parts a and B 2003
DOI: 10.1115/gt2003-38722
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Labyrinth Seal Leakage Flow and Main Flow in an Axial Turbine

Abstract: This paper presents the results of an experimental investigation into the flow in a 1.5-stage low-speed axial turbine with a straight labyrinth seal on the rotor shroud. The paper focuses on the interaction between the leakage flow and the main flow. The experimental program consists of measurements of the three-dimensional properties of the main flow downstream of the rotor trailing edge after the re-injection of the leakage flow. The measurements were carried out using pneumatic five-hole probes and three di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The loss centre due to the tip leakage from the upstream rotor moves together with the recirculating flow towards the suction surface and deep towards mid-span sections. The increase in size and intensity of the tip passage vortex in the next stator due to the influence of the tip leakage flow was also observed in some experimental works [24,25].…”
Section: The Effect Of Leakage Flow (The Case Of Shrouded Blades)supporting
confidence: 53%
“…The loss centre due to the tip leakage from the upstream rotor moves together with the recirculating flow towards the suction surface and deep towards mid-span sections. The increase in size and intensity of the tip passage vortex in the next stator due to the influence of the tip leakage flow was also observed in some experimental works [24,25].…”
Section: The Effect Of Leakage Flow (The Case Of Shrouded Blades)supporting
confidence: 53%
“…Some of the earlier results have been presented in several publications, e.g. Peters et al [14], Giboni et al [15], and Anker and Mayer [16].…”
Section: Introductionmentioning
confidence: 78%
“…Thus, combining simulate and experiment to analyze the characteristics of leakage flow inside turbocharger chamber becomes a critical technical way to guide the sealing structure design. The study of flow characteristics between leakage flow and main flow conducted by Giboni et al indicated that the leakage flow deteriorated the flow field in turbine, resulting in the unstable operation of turbine [15]. It is necessary to seriously take into account the leakage flow in the design or optimization of turbomachinery.…”
Section: Introductionmentioning
confidence: 99%